Active pole bending effect in pole support phase - Fukushima, T.; Nishikawa, S.; Kuniyoshi, Y. (Sports Biomechanics, 2022)
In pole vaulting, model analysis is one of the key methods to increase vaulting height. To date, the effects of athletes` motions during `pole support phase` have been measured and modelled to improve and set new world records. The motions were extracted based on the context of pole bending interaction and parameters to improve vaulting height were investigated. However, due to experimental, mechanical, and sensing restrictions, ranges and interactions of the parameters were poorly addressed. To investigate further, a parameter space must be globally explored. Here, we show parameter sensitivities and interactive effects between initial velocity, pole length, bending amplitude and switching time. From the simulation studies, we found that active pole bending enabled successful pole vaulting with lower initial velocity and longer poles. Vaulting height had a local maximum point at a specific initial velocity and positive bending could control conditions to deliver the local maximum height. Positive bending controls the rising-up speed of the pole and contributes to the verticalisation of the vaulting angle. Negative bending increases the vaulting speed and contributes to the robustness of the vaulting angle. Our results demonstrate how these parameters affect the vaulting performances and suggest how athletes should activate their bodies.